Manajemen Balanced Scorecard Perspektif Learning and Growth dalam Meningkatkan Mutu Pendidik di MTs Negeri 7 Kebumen - Munfingah, Munfingah; Anwar, Sirojul (LPPM IAINU Kebumen, 2023)
Educational institutions need BSC management to improve the quality of learning so that educational institutions can continue to grow and be measured in accordance with the institution's vision, mission, and goals that have been determined. The method used in this research is a descriptive qualitative method with a scientific research approach to Islamic education management. The research results show that school principals formulate strategies through three elements, namely: First, increasing the ability of educators is carried out by analyzing needs in planning, implementing programs, and evaluating development activities. Second, increasing the ability to prepare for developments in information technology by keeping abreast of technological and information developments through training activities, workshops, and peer tutoring. Third, in maintaining the motivation of educators, the principal provides input and appreciation to the teaching staff, while fellow teachers contribute to each other, providing enthusiasm to become even better.